Secuencias de 658 pares de bases (fragmento barcode) del gen citocromo c oxidasa subunidad I (COI) de Culex bidens de Colombia - Laurito, Magdalena (2023)
Arbovirus transmission cycles must be studied locally since both vectors and hosts vary in different regions. Colombia has a highly diverse mosquito fauna. Culex (Culex) bidens is reported here for the first time in Colombia. Because Cx. bidens Dyar and Knab and Cx. declarator Dyar and Knab share a close taxonomic history and because it is difficult to differentiate between them, a morphological and molecular comparison was performed. The male genitalia of three specimens of Cx. bidens from Colombia were mounted on microscope slides and morphologically compared with the male genitalia of Cx. declarator also from Colombia. In Cx. bidens, the individual teeth of the lateral plate are long, straight, laterally directed and sharply pointed; in Cx. declarator these teeth are robust, curved, with convex margins and bluntly rounded. Moreover, DNA was extracted from the same specimens and a fragment of the cytochrome c oxidase subunit I mitochondrial gene was amplified and sequenced. Neither Cx. bidens nor Cx. declarator were clustered in the Neighbour-joining topology, with K2P interspecific divergence between 0.15–1.45%. The circulation of Eastern Equine Encephalitis Virus in Colombia was reported since 1957 and Cx. bidens was suspected to be the vector of this virus during an epizootic in Argentina in 1988. Hybridization between species of the subgenus Culex has been demonstrated, hence the degree of reproductive isolation between Cx. bidens and Cx. declarator should be investigated, as well as their taxonomic status, because they only can be discriminated by a single male genitalic feature and not by nuclear or mitochondrial markers.